2013
DOI: 10.4274/tjh.2012.0180
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of t(15;17) and t(8;21) in a Case of Acute Promyelocytic Leukemia: Review of the Literature

Abstract: Additional chromosomal abnormalities in acute myelogenous leukemia have been identified as one of the most important prognostic factors. Favorable chromosomal changes such as t(8;21), inv(16), and t(15;17) are associated with higher rates of complete remission and event-free survival. Translocation (15;17) characterizes acute promyelocytic leukemia (APL) (French-American-British class M3) in almost all patients. Secondary chromosomal abnormalities are also present in approximately 23%-29% of patients with newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…However, our results showed a frequency that was ∼9% higher than that found in studies from the United States, Europe, Asia, and Australia, but it was 2.5% lower than that reported for the Japanese population ( Supplementary Table S2 ). This fusion gene was prevalent in M2, but it was also detected in M1, M3, M4, and M7, in agreement with other studies, but there are no studies about their clinical impact ( 7 9 , 24 27 ). PML-RARA had a prevalence that was ∼10% higher than that found in studies from the United Kingdom, Germany, Japan, and Austria, but not for Brazil, whose population has a 1.5% lower frequency ( Supplementary Table S2 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, our results showed a frequency that was ∼9% higher than that found in studies from the United States, Europe, Asia, and Australia, but it was 2.5% lower than that reported for the Japanese population ( Supplementary Table S2 ). This fusion gene was prevalent in M2, but it was also detected in M1, M3, M4, and M7, in agreement with other studies, but there are no studies about their clinical impact ( 7 9 , 24 27 ). PML-RARA had a prevalence that was ∼10% higher than that found in studies from the United Kingdom, Germany, Japan, and Austria, but not for Brazil, whose population has a 1.5% lower frequency ( Supplementary Table S2 ).…”
Section: Discussionsupporting
confidence: 88%
“…The preexisting somatic mutations mainly tend to DNA damage, such as TP53 or PPM1D mutations (Martin et al, 2020). Moreover, there were also some cases about co-expression of t(15; 17) and other chromosome translocations, such as t(8; 21) (Uz et al, 2013). While the incidence of chromosomal rearrangements in addition to t(15; 17) was rare, and the role of additional translocations was still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Co-expression of t(8;21) and t(15;17) is rare in APL, with only 6 patients reported at present ( 79 84 ). Neto et al ( 79 ) reported a case of APL-M3V which was sensitive to ATRA treatment, and detected a novel t(8;21) chromosomal aberration between 3 and 18 months after initial treatment.…”
Section: Complex Karyotypementioning
confidence: 95%
“…No ED occurred during primary therapy, despite a high rate of relapse. A favorable response to chemotherapeutic induction indicated that the ATRA and idarubicin and Ara-C induction treatment was suitable for this complex karyotype ( 84 ). Another study also suggested that at the time of diagnosis the rate of M2 leukemic cells could be tested using polymerase chain reaction detection and the alteration of bone marrow cell kinetics may trigger t(8;21) via complex mechanisms following chemotherapy ( 79 ).…”
Section: Complex Karyotypementioning
confidence: 99%